Energy-efficient and low-delay scheduling scheme for low power wireless sensor network with real-time data flows. (2016) - Zhang, Zheng; Li, Zhenbo; Chen, Jiapin; Hu, Shouwei; Wang, Wei
In this paper, we propose an energy-efficient and low-delay scheduling (EELDS) scheme for interruptible preamble sampling-based medium access control (MAC) protocols (e.g., BoX-MAC-2 and X-MAC) in IEEE 802.15.4 wireless sensor network (WSN), which considers energy efficiency while reducing delay and contention in the context of real-time data gathering and remote monitoring applications. It is built on MAC layer and exploits local information to coordinate the MAC schedules of nodes in a slowly-changing topology, just with light overhead. The scheme also considers the adaptation to data aggregation with real-time data flows. Therefore, our scheme allows for much longer network lifetime while satisfying the delay constraints. The implementation and simulation results show the performance of the proposed scheme.